2001
DOI: 10.1046/j.1523-1755.2001.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte injuries exacerbate mesangial proliferative glomerulonephritis

Abstract: Podocyte injury might be an important factor that exacerbates mesangial proliferation and mesangial matrix expansion. The irreversible mesangial alterations caused by consecutive injections of PAN and mAb 1-22-3 may be a novel model that could be used to analyze the mechanism of progressive mesangial alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…There was no evidence of a nephron-to-nephron transfer of the disease at the level of the tubulointerstitium. This conclusion is in full agreement with previous studies of the Thy-1 model (63,64), with studies of several degenerative models of nephron loss (9,46,(65)(66)(67), as well as with studies of human cases (13,68).…”
Section: Relevance Of Tubulointerstitial Processessupporting
confidence: 92%
“…There was no evidence of a nephron-to-nephron transfer of the disease at the level of the tubulointerstitium. This conclusion is in full agreement with previous studies of the Thy-1 model (63,64), with studies of several degenerative models of nephron loss (9,46,(65)(66)(67), as well as with studies of human cases (13,68).…”
Section: Relevance Of Tubulointerstitial Processessupporting
confidence: 92%
“…Preceding minor podocyte injury to this model leads to irreversible mesangial alteration (8), demonstrating the importance of podocytes for the glomerular recovery in this model. These findings suggest that podocytes contribute to maintenance and recovery of the glomerular structure by counteracting the hydrostatic force on the glomerular filtration barrier mechanically.…”
mentioning
confidence: 74%
“…One study showed that minor podocyte injury with puromycin preceding Thy-1 GN induction results in irreversible mesangial lesions (8). Another report demonstrated that mice deficient of podocyte-specific mole- cule CD2-associated protein exhibit mesangial cell proliferation and mesangial matrix expansion (32).…”
Section: Discussionmentioning
confidence: 99%
“…Second, podocyte injury impairs mesangial structure and function. In anti-Thy-1 glomerulonephritis, a reversible self-limiting model in itself, preceding minor podocyte injury with PAN pretreatment results in irreversible mesangial alteration (48). We showed recently that cysteine-rich protein 61 (Cyr61), a potent angiogenic protein that belongs to the CCN family of matrix-associated secreted protein family, is expressed in podocytes and upregulated in anti-Thy-1 glomerulonephritis (20).…”
Section: Discussionmentioning
confidence: 99%